Grey nomads with diabetes self-management on the road - a scoping review - Anita De Bellis; Christine McCloud; Jane Giles; Marc Apolloni; Wendy Abigail; Pauline Hill; Liam McClory (James Cook University, 2021)
Introduction: This scoping literature review explored the characteristics and behaviours of a subset of Australia's older population: 'grey nomads', many who live and travel with type 1 or 2 diabetes mellitus. Grey nomads are people aged more than 55 years, who travel in caravans or motorhomes for extended periods of time around rural and remote areas of Australia. Grey nomads are challenging the established view of ageing in Australia by their lifestyle choices, which include social and economic contribution, independence and furthering of personal fulfilment. However, some evidence suggests that grey nomads experience health issues while in rural locations, which exerts a significant burden on already under-resourced Australian rural health services. This review seeks knowledge on grey nomads' self-management of diabetes while travelling, with the aim of understanding their experiences and identifying support services and strategies that would facilitate improved self-management. Furthermore, this review seeks knowledge of how Australia's rural and remote health services support the nomads with diabetes and the influence of this burgeoning population on such services. Methods: A scoping review methodology provided the methods to map the current evidence concerned with this broad and complex topic. A systematic six-step framework was adopted: identifying the research question; identifying relevant literature; selecting studies; charting the findings; collating, summarising and reporting results; and a final consultation. Results: The grey nomads in this review travelled long distances through the often-harsh Australian countryside where they sought, privacy, isolation, self-sufficiency and a closeness with nature. Although their motivations included life- and health-enhancing experiences, most grey nomads travelled with at least one chronic health condition, which they did not consider as a barrier to adopting a grey nomad lifestyle. However, many were under-prepared for their health needs when in rural or remote Australia. Specific literature concerning grey nomads and self-management of diabetes was not found but salient aspects of diabetes self-management were identified and included a well-developed relationship with their diabetes healthcare provider; a relationship that relied on ongoing communication and support. When travelling, the ability to form or sustain supportive relationships with local health care providers was limited due to sparseness of rural services and the perceived transient nature of the relationship. Increasingly, grey nomads utilised digital technology via telemedicine or social media sites for information and advice on health issues. The local pharmacies in rural and remote locations were also identified as sources of support and services. Conclusion: The literature showed that the grey nomad population had a similar distribution of chronic illness, including diabetes, to that of the general Australian population, but very little was published about how they self-manage conditions when in remote locations where healthcare services were limited. The emerging roles of digital technology and development opportunities for pharmacists offer new and innovative avenues to support grey nomads with diabetes while travelling in rural and remote Australia.